Characterization and validation of Entamoeba histolytica pantothenate kinase as a novel anti-amebic drug target. Issue 1 (April 2018) - Nurkanto, Arif; Jeelani, Ghulam; Yamamoto, Takehiro; Naito, Yoshiko; Hishiki, Takako; Mori, Mihoko; Suematsu, Makoto; Shiomi, Kazuro; Hashimoto, Tetsuo; Nozaki, Tomoyoshi
Abstract: The Coenzyme A (CoA), as a cofactor involved in >100 metabolic reactions, is essential to the basic biochemistry of life. Here, we investigated the CoA biosynthetic pathway of Entamoeba histolytica ( E. histolytica ), an enteric protozoan parasite responsible for human amebiasis. We identified four key enzymes involved in the CoA pathway: pantothenate kinase (PanK, EC 2.7.1.33), bifunctional phosphopantothenate-cysteine ligase/decarboxylase (PPCS-PPCDC), phosphopantetheine adenylyltransferase (PPAT) and dephospho-CoA kinase (DPCK). Cytosolic enzyme PanK, was selected for further biochemical, genetic, and phylogenetic characterization. Since E. histolytica PanK (EhPanK) is physiologically important and sufficiently divergent from its human orthologs, this enzyme represents an attractive target for the development of novel anti-amebic chemotherapies. Epigenetic gene silencing of PanK resulted in a significant reduction of PanK activity, intracellular CoA concentrations, and growth retardation in vitro, reinforcing the importance of this gene in E. histolytica . Furthermore, we screened the Kitasato Natural Products Library for inhibitors of recombinant EhPanK, and identified 14 such compounds. One compound demonstrated moderate inhibition of PanK activity and cell growth at a low concentration, as well as differential toxicity towards E. histolytica and human cells. Graphical abstract: Image 1 Highlights: Pantothenate kinase (PanK) is essential in Entamoeba histolytica parasite. PanK gene silencing caused a significant growth defect, CoA level, and PanK activity. PanK represents an attractive target for new drug development. Potential inhibitors have been found against E. histolytica PanK.